Mechanical and Materials Engineering of Modern Structure and Component Design - Öchsner, Andreas; Altenbach, Holm (Advanced Structured Materials, 2015)
This book presents the latest findings on mechanical and materials engineering as applied to the design of modern engineering materials and components. The contributions cover the classical fields of mechanical, civil and materials engineering, as well as bioengineering and advanced materials processing and optimization. The materials and structures discussed can be categorized into modern steels, aluminium and titanium alloys, polymers/composite materials, biological and natural materials, material hybrids and modern nano-based materials. Analytical modelling, numerical simulation, state-of-the-art design tools and advanced experimental techniques are applied to characterize the materials' performance and to design and optimize structures in different fields of engineering applications.